The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000471933
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Promotes Cell Migration and Invasion, and Inhibits Apoptosis and Autophagy in Colorectal Cancer by activating the p38 MAPK Signaling Pathway

Abstract: Background: Osteopontin (OPN) is highly expressed in colorectal cancer (CRC) and is associated with disease progression in vivo. High levels of OPN have been demonstrated to predict low survival rates in CRC. Autophagy is a process of self-digestion, which is thought to play a significant role in carcinogenesis. However, the mechanisms of OPN's effects on CRC cell autophagy have not been elucidated. Therefore, we aimed to investigate possible mechanisms of OPN's effects on CRC autophagy. Methods: HCT116 cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 40 publications
3
43
0
2
Order By: Relevance
“…This function prevents cell apoptosis from being induced by various stimuli. Secondly, the pathway may indirectly suppress the activity of caspase-3 by activating the inhibitors of apoptosis molecules, including inhibitor of apoptosis and B cell lymphoma-2 family proteins (43,44). Thirdly, the pathway may block the release of mitochondrial cytochrome C and interfere with the activation process of upstream caspase-9, indirectly decreasing the activity of downstream caspase-3 (45).…”
Section: Action Mechanisms Of the Mapk Signaling Pathway In Oral Cancermentioning
confidence: 99%
“…This function prevents cell apoptosis from being induced by various stimuli. Secondly, the pathway may indirectly suppress the activity of caspase-3 by activating the inhibitors of apoptosis molecules, including inhibitor of apoptosis and B cell lymphoma-2 family proteins (43,44). Thirdly, the pathway may block the release of mitochondrial cytochrome C and interfere with the activation process of upstream caspase-9, indirectly decreasing the activity of downstream caspase-3 (45).…”
Section: Action Mechanisms Of the Mapk Signaling Pathway In Oral Cancermentioning
confidence: 99%
“…However, apoptosis during infection can shape a suppressive, autoreactive or protective immune response . OPN seems to play an important physiological role in the efficient development of Th1 immune responses and cell survival by inhibiting apoptosis . These findings indicate that OPN knockdown may reduce inflammation by modulating neutrophil recruitment, decreasing proinflammatory cytokines and increasing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of OPN in mediating fungal keratitis is still not well understood, several studies indicate its role in antifungal immunity. For example, Inoue et al 19 found that OPN is essential in mediating the cluster formation of fungal receptors that detect Pneumocystis and plays a role as an adaptor molecule in the TLR2 and dectin-1 signaling pathways. Nishikaku et al 20,22 found that OPN is involved in granuloma formation and in the severity of P. brasiliensis infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations